Using Running Dictation Game To Improve Grade Ten Students' Understanding On Simple Present Tense In SMA Negeri 2 Pematang Siantar - Fretty Riana Rajagukguk; David Togi Hutahean; Irene Adryani Nababan (CV Putra Publisher, 2024)
This objective of this research is to find out the effect of using Running Dictation Game on Simple Present Tense SMA Negeri 2 Pematang Siantar in the academic year 2022/2023. Through the uses of a quasi-experimental design, this research uses a quantitative method. It has two classes, such as experimental class and control class which use in the research. 353 students in grade ten at SMA Negeri 2 Pematang Siantar make up the population of this research. Students from classes X-2 (experimental class) and X-1 (control class), who choose using the purposive sampling technique and make up the sample for this research. There are 10 multiple-choice questions and 10 essay on the research instrument, including a pre- and post-test that the researcher uses to assess the data. The researcher uses the t-test formula to assess the data. The result of this data shows that the mean score of pre-test in experimental class score is 74.5, while the mean post-test score is 92.7. In the control class, the pre-test mean is 63.2, and the post-test mean is 79.4. After calculating the mean score for both groups and using the t-test formula, the results show that the t-test has the highest significance level in the t-table with 5% level significance (1.807> 1,667). So, using running dictation game to improve grade ten has significant effect to the students’.